2014
DOI: 10.1163/15718182-55680024
|View full text |Cite
|
Sign up to set email alerts
|

A Children’s Rights Perspective on Food Advertising to Children

Abstract: This article applies the United Nations Convention on the Rights of the Child to the regulation of food advertising for the prevention of childhood obesity, evaluating the advertising regulation in six jurisdictions against the principles of the Convention. It finds that the Convention would support strict regulation of food advertising for the prevention of childhood obesity; and in particular that such regulation would be appropriate to the model of co-operation between the state and parents that the Convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…ATC has emerged as a research priority of multiple disciplines, such as paediatric research (Gearhardt and Brownell, 2013), marketing and advertising (Effertz et al, 2019), law and policy (Kunkel et al, 2014), psychology (Coates et al, 2019) and business ethics (Lee and Nguyen, 2013). ATC research provides empirical evidence to support the correlation between exposure to ATC through the different media and food preferences of children (Borzekowski and Pires, 2018); however, the causal link between food ATC and childhood obesity is still debatable (Handsley et al, 2014). The focal point is the unethical and exploitative nature of ATC, taking undue advantage of the limited ability of children to differentiate between entertainment and persuasive intent (Nairn and Fine, 2008).…”
Section: What We Know About Atc – Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATC has emerged as a research priority of multiple disciplines, such as paediatric research (Gearhardt and Brownell, 2013), marketing and advertising (Effertz et al, 2019), law and policy (Kunkel et al, 2014), psychology (Coates et al, 2019) and business ethics (Lee and Nguyen, 2013). ATC research provides empirical evidence to support the correlation between exposure to ATC through the different media and food preferences of children (Borzekowski and Pires, 2018); however, the causal link between food ATC and childhood obesity is still debatable (Handsley et al, 2014). The focal point is the unethical and exploitative nature of ATC, taking undue advantage of the limited ability of children to differentiate between entertainment and persuasive intent (Nairn and Fine, 2008).…”
Section: What We Know About Atc – Analysis and Discussionmentioning
confidence: 99%
“…Therefore, the policy inquiry starts by asking what is being offered to children to eat every day (Mills, 2012). Handsley et al (2014) raised a question regarding why advertisers should not consider developing children as consumers as a form of economic abuse; they strongly supported strict regulations of F&B advertising for the deterrence of its hostile impact on child health. Kunkel et al (2014) found that despite strict compliance with self-regulatory pledges by participating companies, self-regulation was not effective enough regarding curtailing F&B advertising to children; they argued that the potential of unhealthy F&B marketing targeting children is huge, and self-regulation either does not exist or have been ineffective.…”
Section: Rq2mentioning
confidence: 99%
“…Another alternative increasingly being voiced is a rights-based approach to protecting young consumers from marketing techniques and communications that might be misleading or prevent them from leading a happy, healthy life. Citing the UN convention’s rights of the child, Handsley et al (2014) raise the possibility of legally declaring predatory marketing practices by food companies towards young consumers in the digital context as economic exploitation. They advocate that corporations need to use benchmarks, such as those used by the Human Rights Convention, to see how their marketing practices stack up ethically.…”
Section: Implications For Policymentioning
confidence: 99%
“…On deceptive advertisement, few authors (Hoogenraad & Duivenvoorde, 2015;Ippolito, 2003Ippolito, -2004Sax, 2015;Mohd Nor, Sheau, Liew & Rajah, 2014;Handsley & Nehmy, 2014) discussed on the doubt that advertising provides much information useful to consumers or competition. Some fear that without strong and legal constraints, the selling intent behind advertising will lead to considerable deception and consumer harm and competitive forces will not fill in important missing information (Gibson and Taylor, 2005).…”
Section: Viral Marketingmentioning
confidence: 99%